PENGARUH INOVASI LAYANAN DAN MODAL USAHA TERHADAP KINERJA UMKM BIDANG JASA DI DESA SUKAHARJA KECAMATAN TELUK JAMBE TIMUR KABUPATEN KARAWANG - Muhammad Nur Alam; Danang Kusnanto (Institut Teknologi dan Bisnis Dewantara, 2025)
This study aims to identify, analyze, and explain service innovation, business capital, and MSME performance, as well as the influence of both on business performance. Using the Taro Yamane formula with a 5% confidence level, a sample of 114 MSMEs was obtained from the 159 MSMEs. This quantitative research employs multiple regression analysis with the help of Excel and SPSS23 for descriptive and verification analysis. The results indicate a partial and simultaneous influence between service innovation (X1), business capital (X2), and business performance (Y). Service innovation has an average value of 339 (moderately agree), indicating that the MSMEs in Sukaharja Village generally understand the importance of innovation in enhancing service quality. Business capital has an average value of 320 (moderately agree), indicating an adequate understanding of the importance of sufficient capital to run a business. Business performance also falls under the criteria of